2022
DOI: 10.5435/jaaos-d-22-00419
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Toe Walking: An Update on Natural History, Diagnosis, and Treatment

Abstract: Toe walking is a common presenting report to an orthopaedic practice. Evaluation of a child with toe walking includes a thorough history and physical examination to elucidate the diagnosis. When no other diagnosis is suspected, a diagnosis of idiopathic toe walking is often given. Despite the high prevalence of the condition, there is notable controversy of the nomenclature of the disease. Recent research has shed more light on both the natural history and the genetic basis. The use of motion analysis, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Finally, the lack of consensus in results is apparent due to the heterogeneity in methodologies, as discussed by [40] in their systematic review of outcomes and assessment tools, as well as in Bauer's (2022) [30] and Williams' (2020) [52] findings, which identified a lack of consensus among healthcare professionals regarding evidence-based therapies. Heterogeneity is seen in populations across studies [32,37,45], the type of severity classification used [29,32,42], previous treatments [46,47], and different exclusion criteria [19,42], among other differences, making results comparison unfeasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the lack of consensus in results is apparent due to the heterogeneity in methodologies, as discussed by [40] in their systematic review of outcomes and assessment tools, as well as in Bauer's (2022) [30] and Williams' (2020) [52] findings, which identified a lack of consensus among healthcare professionals regarding evidence-based therapies. Heterogeneity is seen in populations across studies [32,37,45], the type of severity classification used [29,32,42], previous treatments [46,47], and different exclusion criteria [19,42], among other differences, making results comparison unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…Bauer et al (2022) [30] introduced a descriptive classification for children who walk on their toes. In a straightforward manner, they divided it into toe walking during developmental stages, ITW with autism, congenital tendon contracture, habitual persistent ITW (without contracture), and finally, persistent ITW with contracture (Figure 3).…”
Section: Classification Of Itwmentioning
confidence: 99%
See 1 more Smart Citation
“…This review paper from Portland (Oregon, USA) is a recommended read for interested surgeons as it thoroughly discusses the current treatment and literature surrounding idiopathic toe walking. 4 Gait motion analysis and multisegment foot modelling are recommended to differentiate mild forms of cerebral palsy and to evaluate treatment outcomes; centres without access to these modalities would be wise to generate these with neighbouring centres in order to offer the best decision-making for patients. The review concluded that early treatment should appropriately be reassurance only, as the majority will resolve spontaneously and the prevalence of the condition is relatively high.…”
Section: Idiopathic Toe Walking: An Update On Natural History Diagnos...mentioning
confidence: 99%
“…Although ITW has been known for more than half a century, we still do not know much about its etiology [14,15]. Currently, there is a growing interest in the diagnosis, treatment, classification, and causes of ITW.…”
Section: Introductionmentioning
confidence: 99%